1996
DOI: 10.1073/pnas.93.20.10723
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced forms in the cytoplasmic domain of the human growth hormone (GH) receptor regulate its ability to generate a soluble GH-binding protein.

Abstract: Alternatively spliced forms in the cytoplasmic domain of the human growth hormone (GH) receptor regulate its ability to generate a soluble GH-binding protein ( ABSTRACTThe mechanism underlying the generation of soluble growth hormone binding protein (GHBP) probably differs among species. In rats and mice, it involves an alternatively spliced mRNA, whereas in rabbits, it involves limited proteolysis of the membrane-bound growth hormone receptor (GHR). In humans, this latter mechanism is favored, as no transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 51 publications
4
73
0
4
Order By: Relevance
“…That is, despite infectious overexpression: 1) rbGHR del 297-406 and rbGHR 1-274-Myc-His underwent basal and PMA-induced cleavage and GHBP shedding with kinetics similar to what we previously showed; 2) PMA-induced proteolysis and GHBP shedding was inhibited by IC3; and 3) GH antagonized PMA's ability to cause receptor cleavage. In addition, rbGHR 1-274-Myc-His is analogous to a naturally occurring alternatively spliced GHR form that is known to effectively yield proteolytically shed GHBP in other systems (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, despite infectious overexpression: 1) rbGHR del 297-406 and rbGHR 1-274-Myc-His underwent basal and PMA-induced cleavage and GHBP shedding with kinetics similar to what we previously showed; 2) PMA-induced proteolysis and GHBP shedding was inhibited by IC3; and 3) GH antagonized PMA's ability to cause receptor cleavage. In addition, rbGHR 1-274-Myc-His is analogous to a naturally occurring alternatively spliced GHR form that is known to effectively yield proteolytically shed GHBP in other systems (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a naturally occurring GHR splice variant lacking nearly the entire cytoplasmic domain generates substantial amounts of proteolytically shed GHBP (31,32). For remnant purification, we designed and adenovirally expressed a rbGHR mutant, rbGHR 1-274-Myc-His , that encodes the first 274 residues of the receptor followed by C-terminal Myc and His tags.…”
Section: Adenovirally Expressed C-terminal Epitope-tagged Rbghr Cytopmentioning
confidence: 99%
“…Recent studies have, however, suggested that the circulating binding protein is also cleaved from a truncated receptor lacking 97.5% of the intracellular part, which is a result of an alternatively spliced mRNA (27,28). High levels of GHBP have been found in conditions with low GH levels, including simple obesity (7,29) and vice versa in, for example, acromegaly and insulin-dependent diabetes mellitus (7,(30)(31)(32)(33).…”
Section: Figurementioning
confidence: 99%
“…24, and data not shown); this latter finding therefore further supports our molecular model inferring a key role of these sequences of retroviral origin in the genesis of GHRd3 transcripts. Such a species-specific GHR structural difference, which underlies the existence of the sole GHRfl allele in several species, relates to the evolutionary differences of the mechanisms by which the GHR gene gives rise to a soluble growth hormone-binding protein (29,30), thereby making this gene a particularly interesting model to investigate its encoded isoforms through evolution.…”
Section: Otype (Presence Of Ghrfl And/or Ghrd3 Alleles) and The Exprementioning
confidence: 99%